Variations of Time for Composting Market Organic Waste Using Aerobic Microorganisms - Kurniati Kurniati; Ade Mulawarman; Dwi Ahrisa Putri (Agro Bali : Agricultural Journal, 2022)
The use of fertilizers in agriculture is an absolute must, both organic fertilizers and inorganic fertilizers. Considering the increasing price of inorganic fertilizers, innovation is needed to make organic fertilizers from easily obtained materials, one of which is market organic waste. Among the aerobic microorganisms used are lignolytic, cellulotic, proteolytic, lipolytic and aminolytic which are capable of changing compost in time. The purpose of this study was to analyze the right time in the composting process so as to produce a maximum source of essential nutrients. The research method or stages used is to divide the composting time into 4 parts, namely 5 weeks, 6 weeks, 7 weeks and 8 weeks. The results showed that the C-Organic content in the 5-7 weeks composting phase met the minimum SNI standards, while in the 8-week composting phase it is below the minimum standard of SNI. Phosphorus content is also above the minimum limit of the standard determined by SNI, Meanwhile, Potassium and Nitrogen are below the minimum SNI standard. The content of secondary macronutrients such as Calcium, Magnesium, and Sodium does not exceed the maximum limit set by SNI.